The Game as the Way of Personal Identity Development - L. A. Belyayeva; O. N. Novikova (Russian State Vocational Pedagogical University, 2015)
The paper suggests the game interpretation as the universal and phenomenal way of developing personal identity by a relaxed participation in game activity. Unlike the extended definitions of game as a culturalogical and pedagogical phenomenon, the authors suggest the game analysis in philosophical perspective revealing its existential status. Being the active form of personal existence, the game facilitates self-awareness by means of self-understanding and self-determination in the course of game activity developing the attitude of «I am another one», and giving a chance to experiment with personal identity, taking and playing various social and cultural roles. The existential significance of games activating self-understanding and meaning of self-existence is growing nowadays, given pluralism and reassessment of values.